The Effect of Residual Swelling after Drying on Internal Bond in OSB - Radosław Mirski (University of Zagreb, Faculty of Forestry and Wood Technology, 2012)
The study determined the effect of non-recoverable thickness swelling (NTS) on internal bond in oriented strand boards (OSB). The tests were conducted taking into consideration different time variants, ranging from 1 to 70 h, of soaking in water at 20ºC. The analysis of the results recorded for measured non-recoverable thickness swelling indicates that the observed reduction of strength is a result of changes occurring in the core of boards. Moreover, a linear IB/NTS dependence was observed for OSB/3 and OSB/4 of 15 mm in thickness.